(untitled) (Impetus, 2021)
There is sufficient evidence that physical inactivity is one of the factors that can contribute to obesity and other chronic and metabolic risk diseases, for this reason it is necessary to interrupt sedentary time, in order to have a better quality of life. The objective of this research was to know the levels of physical activity produced by an intervention with active breaks during the working day. The results show that the female gender was the one that presented the greatest change through the intervention process, taking into account that it had a greater number of intervened subjects, for a total of 29 being (81% of the total), and the male had 7 administrative (19% of the total). Regarding the level of PA, the low category decreased by five administrative (14%), the moderate category increased by two subjects (6%), and the high category increased by three subjects (8%). In this way, the IPAQ can be identified as an ideal instrument when conducting research that requires measuring the level of physical activity in a population.